MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI MODEL ACCELERATED LEARNING BERBANTUAN MEDIA INTERAKTIF - Sitria Jemin; Tedy Machmud; Lailany Yahya (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to improve students’ mathematical problem solving abilities in quadratic equation material through an accelerated learning model assisted by interactive media. This classroom action research was conducted at SMP Negeri 8 Gorontalo City for the 2023/2024 academic year. The research subjects were 25 students in class IX-4. The data collection techniques used are observations and tests. This research lasted for 2 cycles. From the results of observations, teacher activities increased, from 67,31% in cycle I of 87,5% in cycle II with an increase 0f 20,19%. Furthermore, the results of observations of student activities increased, from 66,27% in cycle I to 85,41% in cycle II with an increase of 19,14%. Students’ mathematical problem solving abilities also increased from 56% in cycle I to 84% in cycle II with an increase of 28%. From the research above, it can be conclued that the accelerated learning model asissted by interactive media can improve students’s mathematical problem solving abilities in quadratic equation